Carcinoma larynx with thyroid gland metastasis: a rare case report - Kalloli, Mahesh; Gupta, Ankit; Patil, Rashmi S.; Pandey, Kritika; Garg, Kavya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Thyroid gland (TG) metastasis by laryngeal cancer is uncommon. However, now a days following concept of ‘organ preservation’, so ipsilateral hemithyroidectomy is not required in every case with total laryngectomy (TL) for laryngeal cancer. Studies for T3 and T4 laryngeal cancer having, anterior commissure involvement, transglottic growth or subglottic extension indicates thyroidectomy in the majority of cases. Hemithyroidectomies are linked to hypothyroidism in 23–63% of cases and hypoparathyroidism in 25–52% of cases. There is no recognized link between tumour differentiation and TG involvement. According to reports, the prognosis in cases of TG involvement is poor. The tumour differentiation determines whether the spread is contiguous or noncontiguous. Contiguous spread is more likely in well-differentiated carcinomas, while non-contiguous spread is more likely in poorly or moderately differentiated carcinomas. Anatomically, direct TG invasion is only possible through extralaryngeal soft tissue, which includes the cricothyroid and cricopharyngeus muscles. Non-contiguous spread only possible through lymphovascular invasion which is not necessarily, but seen in 87-91% of cases with subglottic extension over 10 mm, as seen in our case also.